Absence of Ankle Stiffening While Standing in Focus and Cognitive Task Conditions in Older Adults. Issue 2 (3rd March 2020) - Richer, Natalie; Ly, Kien; Fortier, Noémy; Lajoie, Yves
Abstract: Research suggests that an external focus or cognitive task may improve postural control. Removing attention from movement production may promote automaticity, or the tasks may promote ankle stiffening. To investigate these two theories, twenty older adults stood while performing baseline standing, internal focus, external focus, and two cognitive tasks. Changes in postural control occurred in external focus and cognitive task conditions compared to baseline and internal focus, while no change occurred in cocontraction indices. This suggests that an external focus and cognitive task can improve postural control in older adults. Since no change occurred in cocontraction indices across conditions, this suggests that stiffening cannot explain these changes. Instead, changes could be due to automaticity of sway.